Lossless direct path reinforced bidirectional DC-DC converter for on-board charger in electric vehicle - Veerakgoundar Veeramani; Subramaniam Senthilkumar; Chandrasekharan Sowthily (Serbian Journal of Electrical Engineering)
A DC-DC converter plays a vital role in the On-Board Charger for Electric Vehicles (EVs). Also, having the capability for bidirectional power flow for a DC-DC converter is essential for EVs to transfer power from Vehicle-to-Grid (V2G) and Vehicle-to-Vehicle (V2V). In this context, this paper proposes a bidirectional DC-DC converter for the On-Board Charger for Electric Vehicles (EVs). The proposed DC-DC converter has two paths: a lossy partial path through two bridges, a high-frequency transformer, and a lossless direct path directly connecting the source to the output. A 7.8 kW DC-DC converter is developed in MATLAB/Simulink. The performance of the converter is analysed for various operating scenarios. Further, a scaled-down hardware prototype of the proposed converter with a power rating of 600 W has been developed. The dSPACE controller is used to control the power flows. The prototype is tested under various operating conditions. The experimental and simulation results show that the power flow through the direct path is around 58 % and through the partial path around 42 %. Due to this, the overall converter efficiency of 97.8% during charging and 95.6 % during discharging cycles has been achieved. Also, as only 42 % of power flows through the partial path, all the components' ratings and sizes are significantly reduced. Also, the distinguishing feature is its bidirectional power flow capability, making the EV capable of V2V and V2G power transfer. Hence, the proposed DCDC converter is an efficient and compact solution for an On-Board Charger for EVs.